Self-aberration in high-brightness uniformly charged particle beams - Vitaliy Goryashko; Anatoliy Opanasenko; Kazuaki Togawa (Results in Physics)
We show theoretically and experimentally a slice emittance growth in a uniformly charged electron beam in static, and linear in space, electromagnetic fields of the SACLA injector. The Coulomb field of the electrons in a beam creates a linear correlation between the electrons in the transverse phase space. The magnetic field of a solenoid lens first transfers this ‘transverse correlation’ into a ‘longitudinal one,‘ and then back to the transverse plane in an amplified fashion. As a result, the particle momentum exchange between the longitudinal and transverse degrees of freedom in the magnetic field leads to a nonlinear deformation of the transverse phase space of the beam.